PENINGKATAN JARINGAN TRANSPORTASI DI PROVINSI KALIMANTAN TIMUR DALAM MENDUKUNG AKSESIBILITAS WILAYAH - Budi Sitorus; Tulus Irpan Harsono Sitorus; Subandi Subandi (Institut Transportasi dan Logistik Trisakti, 2016)
As one of the gates of development in eastern Indonesia, East Kalimantan Province consists of 14 regencies/ cities with commodity timber, palm oil and coal is a high per capita income of the province and the sixth largest contributor to GDP (6.08%) in Indonesia. The road network has not been able to reach the economic activity in the north and west, not all meet the requirements of the technical feasibility of such strength that resulted in damage to roads and major loss is a problem.The research objective is to formulate recommendations for the development of road transport anticipate growth in East Kalimantan province.Data collection through literature review, the results of research and related scientific publications. Descriptive analyzes were conducted to propose solutions evaluative transportasai development of effective road.Result of the research is to improve road transport services in the North East Kalimantan, East Kalimantan Central Kalimantan South East, the construction and upgrading of roads to reach districts in accordance with the carrying capacity of the traffic load, increase the accessibility index, the construction of freight and passenger terminal and bridge weigh in the order of priority locations, increasing support for MP3EI, KEK and KPI.